2022
DOI: 10.1111/pai.13637
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of Xpert ultra for childhood tuberculosis: A preliminary systematic review and meta‐analysis

Abstract: Diagnosis of childhood tuberculosis (TB) is challenging. Xpert MTB/RIF and the new version Xpert MTB/RIF Ultra (Ultra) are molecular tests currently used to rapidly identify the infection. We reviewed the literature for the accuracy of Ultra assay in the diagnosis of tuberculosis and rifampicin resistance in children. We conducted a full search in PubMed, Web of Science (WOS), Embase, and Scopus, up to April 2021. A bivariate random‐effects model was used to determine the pooled sensitivity and specificity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…4 The recently released Xpert Ultra cartridge was developed for increased sensitivity and should provide added value in children with paucibacillary TB. 17 As previously reported, 18 the Xpert Ultra showed a high sensitivity (84.9%) in patients with confirmed TB in the present study, which is consistent with the comparable LOD for liquid culture. However, the low positive rates of MTB culture (26.0%) and Xpert Ultra (31.0%) in all of the enrolled subjects with active TB in the present study suggested a low bacterial load in the samples of the children.…”
Section: Discussionsupporting
confidence: 91%
“…4 The recently released Xpert Ultra cartridge was developed for increased sensitivity and should provide added value in children with paucibacillary TB. 17 As previously reported, 18 the Xpert Ultra showed a high sensitivity (84.9%) in patients with confirmed TB in the present study, which is consistent with the comparable LOD for liquid culture. However, the low positive rates of MTB culture (26.0%) and Xpert Ultra (31.0%) in all of the enrolled subjects with active TB in the present study suggested a low bacterial load in the samples of the children.…”
Section: Discussionsupporting
confidence: 91%
“…Another study by Signorino et al . suggested that the reason for the low specificity of the Xpert Ultra may be attributed to the unsatisfactory quality of the culture method, as a reference test, and needs further investigation [ 47 ]. Donovan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that Xpert Ultra is a potential gamechanger with more advantages than Xpert in TBM diagnosis. Xpert Ultra has increased sensitivity (including accuracy of RIF resistance testing), and detection of MTB in smear-negative, paucibacillary, paediatric, CSF, and other specimens of extrapulmonary TB ( Kaswala et al, 2022 ; Signorino et al, 2022 ; Sun et al, 2022 ). In 2017, WHO recommended the use of Xpert Ultra to replace Xpert in diagnosing TBM ( Bahr et al, 2018 ; Rindi, 2022 ).…”
Section: Nucleic Acid Amplification Testsmentioning
confidence: 99%